Values of Moderation in Local Musical Traditions: Learning Religious Moderation from the Massamper Putri Tradition in the Multireligious Sangihe Community - Wibowo, Markus; Nagauleng, Andi Mukarramah (Al-Ulum, 2025)
This study investigates the Massamper Putri musical tradition as a cultural medium for internalizing religious moderation within the multireligious community of the Sangihe Islands, Indonesia. This research is important because it highlights local cultural practices as effective, lived approaches to fostering interreligious harmony beyond formal religious instruction. Using a qualitative ethnographic method, data were collected through participant observation, in-depth interviews with performers, cultural leaders, and interfaith figures, as well as documentation of performances and musical scores. The findings show that the musical structure of Massamper Putri—characterized by responsorial singing, four-part vocal harmony, lyrical repetition, and participatory tempo—creates an inclusive and egalitarian social space. The lyrics convey universal spiritual values such as gratitude, togetherness, and respect, enabling participation across religious boundaries. This study concludes that Massamper Putri functions as a form of lived religious moderation that strengthens social cohesion in a multireligious society.